Self-Compatibility Crosses of Several Cocoa Clones - Agung Wahyu Susilo (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2006)
Self compatibility cross in cocoa is a useful criterion in utilizing germplasm collection. Evaluation of self-compatibility crosses on cocoa clones has been carried out in Kaliwining Experimental Station of ICCRI by treating artificial self-pollination. The observed clones were TSH 858, ICS 60, ICS 13, UIT 1, KW 162, KW 165, KW 163, DR 1, DR 2, DRC 16, DRC 15, KKM 22, Na 32, Na 33 and DR 38. Self-compatibility crosses were identified by percentage of fruit set evaluated during 6 consecutive weeks after pollination. The results showed that the percentage of fruit set were significantly different among clones in the range of 0—46.34%. Three groups of compatibility of cocoa clones were identified i.e. first, self-incompatible clones of DR 1, Na 32, Na 33; second, partially self compatible clones of DR 38, TSH 858, ICS 60, ICS 13, UIT 1, KW 162, KW 165, KKM 22; and third, self-compatible clones of DR 2, DRC 16,DRC 15, KW 163. Clones which perform self-incompatible and partially self-compatible furthermore can be used as female parents in the production of hybrids. Key words: self-compatibility, Theobroma cacao, clones.